Assessing Sangguniang Kabataan Programs: A Baseline Study in Developing a Comprehensive Plan for the Development of the Youth in Cuenca, Batangas - Renniel Jayson Jacinto Rosales (Universal Journal of Educational Research)
The Sangguniang Kabataan is an essential part of the government to develop the youth in the society and to encourage a meaningful youth participation in different sectors in the community. This study assesses the Sangguniang Kabataan performance in Cuenca, Batangas as it encapsulates the strength and weaknesses of the programs together with the needs, comments, and suggestions of the youth as guided by the National Youth Commission’s Nine Centers of Meaningful Youth Participation in line with some selected United Nations Sustainable Developmental Goals through a mixed-method study. The study uses the responses of 250 youth participants from 20 barangays which revealed that their assessments put the programs, projects, and activities of the Sangguniang Kabataan on the lower threshold of the verbal interpretation “Agree” while the qualitative side of the survey revealed the priority needs of the youth. The study suggested a thematic development plan to be used as a framework for the next proposal of the SK officials, namely: Assistance, Developmental, and Social Transformation programs, projects, and activities.